Analysis of the Converter Synchronizing Method for the Contribution of Battery Energy Storage Systems to Inertia Emulation - Andrés Peña Asensio (Energies, 2020)
This paper presents a comprehensive analysis of the effect of the converter synchronizing methods on the contribution that Battery Energy Storage Systems (BESSs) can provide for the support of the inertial response of a power system. Solutions based on phase-locked loop (PLL) synchronization and virtual synchronous machine (VSM) synchronization without PLL are described and then compared by using time-domain simulations for an isolated microgrid (MG) case study. The simulation results showed that inertial response can be provided both with and without the use of a PLL. However, the behavior in the first moments of the inertia response differed. For the PLL-based solutions, the transient response was dominated by the low-level current controllers, which imposed fast under-damped oscillations, while the VSM systems presented a slower response resulting in a higher amount of energy exchanged and therefore a greater contribution to the support of the system inertial response. Moreover, it was demonstrated that PLL-based solutions with and without derivative components presented similar behavior, which significantly simplified the implementation of the PLL-based inertia emulation solutions. Finally, results showed that the contribution of the BESS using VSM solutions was limited by the effect of the VSM-emulated inertia parameters on the system stability, which reduced the emulated inertia margin compared to the PLL-based solutions.